2016
DOI: 10.1038/srep35281
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of serum B vitamins levels and oesophageal and gastric cancers in China

Abstract: B vitamins play an essential role in DNA synthesis and methylation, and may protect against oesophageal and gastric cancers. In this case-cohort study, subjects were enrolled from the General Population Nutrition Intervention Trial in Linxian, China. Subjects included 498 oesophageal squamous cell carcinomas (OSCCs), 255 gastric cardia adenocarcinomas (GCAs), and an age- and sex-matched sub-cohort of 947 individuals. Baseline serum riboflavin, pyridoxal phosphate (PLP), folate, vitamin B12, and flavin mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…People with a higher level of riboflavin (HR Q4 vs. Q1 0.56, 95% CI 0.41-0.75) or B12 had a significantly lower risk of ESCC. 35 In another investigation on three polymorphisms in two genes that code for enzymes that require folate and B12 as cofactors, MTRR A66G, MTHFR C677T, and MTHFR A1298C, we found that individuals with the MTHFR 677TT genotype had significantly higher combined ESCC/gastric cardia cancer risks (RR 1.45, 95% CI 1.02-2.05) than those with CC or CT genotypes. Compared to subjects with the MTRR 66AA genotype, subjects with the AG or GG genotypes had a significantly higher risk of ESCC (RR 1.59, 95% CI 1.04-2.42).…”
Section: -Hydroxyvitamin Dmentioning
confidence: 74%
See 1 more Smart Citation
“…People with a higher level of riboflavin (HR Q4 vs. Q1 0.56, 95% CI 0.41-0.75) or B12 had a significantly lower risk of ESCC. 35 In another investigation on three polymorphisms in two genes that code for enzymes that require folate and B12 as cofactors, MTRR A66G, MTHFR C677T, and MTHFR A1298C, we found that individuals with the MTHFR 677TT genotype had significantly higher combined ESCC/gastric cardia cancer risks (RR 1.45, 95% CI 1.02-2.05) than those with CC or CT genotypes. Compared to subjects with the MTRR 66AA genotype, subjects with the AG or GG genotypes had a significantly higher risk of ESCC (RR 1.59, 95% CI 1.04-2.42).…”
Section: -Hydroxyvitamin Dmentioning
confidence: 74%
“…We investigated the associations between B vitamins and related genes with ESCC using serum samples collected in the NIT cohort. People with a higher level of riboflavin (HR Q4 vs. Q1 0.56, 95% CI 0.41–0.75) or B12 had a significantly lower risk of ESCC . In another investigation on three polymorphisms in two genes that code for enzymes that require folate and B12 as cofactors, MTRR A66G, MTHFR C677T, and MTHFR A1298C, we found that individuals with the MTHFR 677TT genotype had significantly higher combined ESCC/gastric cardia cancer risks (RR 1.45, 95% CI 1.02–2.05) than those with CC or CT genotypes.…”
Section: Biomarker Explorationmentioning
confidence: 99%
“…Based on our inclusive criteria mentioned in Materials and Methods, 46 articles were eventually included in our meta-analysis. Among all the selected studies, 19 were conducted in patients of esophageal cancer [ 12 - 30 ], 21 were in patients of gastric cancer [ 12 , 14 , 15 , 22 , 26 , 28 , 31 - 45 ] and 12 were in patients of pancreatic cancer [ 46 - 57 ]. Figure 1 shows the eligible selecting process.…”
Section: Resultsmentioning
confidence: 99%
“…Probands of 4 studies were in American participants [ 15 , 26 , 28 , 29 ], 5 in Chinese [ 12 , 14 , 17 , 19 , 30 ] and 5 in Europeans [ 13 , 16 , 18 , 23 , 27 ]. In terms of the study design, 2 were cohort studies [ 12 , 15 , 18 ] and 17 were case-control studies [ 13 , 14 , 16 - 25 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation